CLINICAL PRESENTATIONS AND COMPLICATIONS OF GUILLAIN BARRE SYNDROME IN CHILDREN WELFARE TEACHING HOSPITAL - Al-Nadawi, Mahjoob N.; Al-Zuhairi, Husam Thaaban; Hussein, Hafadh Jaleel; Alwan, Yusra Fayyadh (AL-Kindy College Medical Journal, 2016)
Background: Guillain Barré syndrome is an acute inflammatory demyelinating disease of the peripheral nerves. Its synonyms are: acute inflammatory demyelinating polyradiculoneuropathy, idiopathic polyneuritis, acute infective polyneuropathy and post infections polyneuritis. Objectives: We attempt to study the clinical presentations and complications in patients with GBS who were admitted to children welfare Teaching Hospital and to compare the results with the other studies.Type of the study: A retrospective study.Methods: A study done on seventy patients with GBS who were admitted to children Welfare Teaching Hospital in Medical City-Baghdad from different parts of Iraq between January 2002-December 2006.Results: Forty (57.14%) of them were males and 30(42.86%) were females, a male to female ratio 1.33:1. There were more cases during winter months. Antecedent events were found in 44 patients (62.86%),26 patients (37.14%) had no history of antecedent events. It was found that 24 patients (34.3%) had only bilateral lower limbs weakness and 46 patients (65.7%) had both bilateral lower and upper limbs weakness. Sensory manifestations occurred in 35 patients (50%). Cranial nerves involvement was observed in 25 patients (35.7%). Autonomic nerves involvement was observed in 9 patients (12.9%). Respiratory muscles were involved in 20 patients (28.6%), 11 patients (15.7%) were admitted to the RCU and needed ventilator setting, 3 patients (4.28%) died in RCU. The results were compared with similar studies from other parts of the world.Conclusions: This study showed that there is no specific pattern of motor weakness involvement and all cases show symmetrical muscle weakness.Bulbar nerves (glossopharyngeal and vagus nerves) involvement is the commonest cranial nerve involvements.Autonomic nerves involvement and respiratory muscles involvement are the main cause of death in GBS. GBS patients should be admitted to the hospital and RCU with ventilator setting should be available along with well trained medical staff. Because the disease may run a prolonged course, we recommend close follow up of the patient to see the end result at that time.